Постнекласична парадигма взаємодії особистості зі світом шляхом її духовного саморозвитку - Колісник, О. П.; Kolisnyk, O. P. (Волин. нац. ун-т ім. Лесі Українки, Ін-т соц. та політ. психології АПН України, 2011)
Півкулі головного мозку діють рецепрокно: ліва розвиває понятійно-логічний розсудок, права − образноінтуїтивний розум. Лівопівкульовий розсудок і правопівкульовий розум доповнюють один одного в напрямку гармонійного функціонування складної системи “людина−світ”. Західна культурна парадигма через знакові системи формує застарілу дискретнологічну картину світу в людини, на її становлення працює традиційна система освіти країн Заходу. Медитація − основа духовних практик, які репрезентують нерелігійну духовність, формує континуально-інтуїтивний розум, відсутня в традиційній освіті навіть психологів. Для активації людського потенціалу особистості, для становлення творчої її участі у вирішенні глобальних проблем людства, для її переходу в постнекласичну парадигму взаємодії зі світом у навчальний процес психологів потрібно ввести медитативні духовні практики, а вчителями мають бути спеціально відібрані й підготовані викладачі психології. Development of the personality contains the process of sense formation, which reflects the social values. Spiritual and sensual development of the personality is determined by the degree of her/his contact with super-personality values, which are owned and transformed into senses. The dominant sense of the sense hierarchy subordinates other senses and determines the life sense of the personality. The life and activity of the personality depends on his/her capability to transform sense hierarchy into real life activity. The protection of the impulsive activity is characterized be formation of self-control, which is derived from the results of social control. Self-control is reflected into consciousness and self-consciousness of the personality, which contribute a lot to the physical and mental activity of the personality. Mental activity contains concepts, which reflect discreet and conflictive reality. In the process of early ontogenetic and social development the personality forms adaptation to the world and human culture. It develops the consciousness of the personality, which comprises the self-conception. In the following stages of the ontogenetic development the individual world picture is formed as a result of the specific social influences. The spiritual stream of psychic solves the contradiction between spontaneous hierarchy of senses and meaningful self-conception. The spiritual stream of psychic determines the super-personality values and the necessity of their realizing. The spiritual stream of psychic causes the misidentification of the personality with self-conception and identification with super-personality values.
Post Non-classical Paradigm of Personal External Interac-tion with the World of Spiritual Selfdevelopm
Keywords: духовність; духовна практика; самість; потоки психіки; ступені духовного розвитку; смисл; ієрархія смислів; особистість; “Я”; парадигма; постнекласична наука; spirituality; spiritual practice; psycic streams; self; levels of spiritual development; sense; hierarchy of senses; personality; paradigm; postnonclassic science